Comparative Study of Rock Mass Classification Systems: A Case Study of Nagdhunga-Naubisea Road Tunnel - Joshi, Parkash Chandra (Himalayan Journal of Applied Science and Engineering, 2024)
Ground classification systems have been widely used to characterize the soil or rock mass for the analysis and design of underground structures. Deformation characteristics of rock mass around the underground excavation boundary varies according to types of rock and their properties, in situ stress condition and types of support used. Broadly used classification systems for underground structures are Rock Mass Rating (RMR) and Rock Quality Index (Q- Systems) but in-case of the Nagdhunga-Naubisea road tunnel Nippon Expressway Company Limited used NEXCO-System. Literally, the NEXCO classification is based on the velocity of elastic wave, geological condition, boring core condition, competence factor, stability of tunnel face and convergence. However, in-case of Nagdhunga-Naubisea road tunnel, grade point is computed using the similar parameters that are used in RMR- System and Q-System. This research focuses about comparison between ground classification from RMR, Q-system and NEXCO system. The geological descriptions obtained from project office at chainages (0+497 to 0+502), (0+508 to 0+513), (0+581.8 to 0+587.8) and (0+584.2 to 0+590.2) were used to correlate the relationship between RMR, Q-system and NEXCO system of rock mass classification systems. Results showed that from RMR, the ground classification is “poor” at all the chainages whereas from Q-system is “very poor” at chainage (0+508 to 0+513) and “poor” at other chainages. Similarly, from NEXCO- system it was found that “DII” at chainages (0+497 to 0+502) and (0+508 to 0+513) and CII for chainages (0+581.8 to 0+587.8) and (0+584.2 to 0+590.2). These results revealed that the ground classification from NEXCO as DII is similar to poor from RMR and poor or very poor from Q system where as CII from NEXCO is similar to poor from both RMR and Q system.